Influence of leader social capital on product innovation - Yen, Pham Ngoc; Phuong, Ha Thi Thu; Trung, Nguyen Tan; Thanh, Do Minh; Anh, Le The (Edelweiss Applied Science and Technology, 2025)
This study was conducted with the aim of analyzing, evaluate and measuring the impact of leadership social capital on product innovation of plastic and packaging firms in Hanoi and neighboring provinces through survey results. Employees of packaging and plastic companies in Hanoi and the surrounding regions make up the survey participants. 305 respondents made up the study’s sample, and the research subjects included accountants, salespeople, office workers, and other employees of plastic and packaging companies. Both qualitative and quantitative research techniques are employed by us. Regression models, correlation analysis, EFA analysis, and scale reliability analysis utilizing Cronbach’s alpha coefficient were among the quantitative research techniques used using SPSS software. Research results show that leader social capital: colleague ingredients (LSC-C) and leader social capital: association of occupation ingredients (LSC-AOI) positively influence product innovation. However, no influence of leader social capital: business partners’ ingredients (LSC-BP) on product innovation was found (PI = 0.363*LSC-C + 0.358*LSC-AOI). Based on this result, the study proposes some recommendations for plastic and packaging firms and employees.